EFISIENSI TEKNIS USAHATANI BAWANG MERAH DI KECAMATAN KETAPANG KABUPATEN LAMPUNG SELATAN - Hardini Tristya; Ktut Murniati; Muhammad Irfan Affandi (Lampung University, 2018)
This study aims to analyze technical efficiency of onion farming and the factors that influence the technical inefficiency of onion farming. This research is conducted purposely in Ketapang Sub-district. The respondents are 49 farmers collected by sensus method. He research data is taken in September to November 2016. The technical efficiency is measured by frontier production function and estimated by Maximum Likelihood Estimation (MLE) method with Frontier 4.1c computer program. The estimation of factor that influences the technical inefficiency is applied by linear regression model simultaneously obtained by using the frontier production function. The results showed that the average of technical efficiency of onion farming in Ketapang Sub-district was 0.93 which meant very efficient. Furthermore, the factors that significantly influenced the technical inefficiency of onion farm in Ketapang Sub-district were the farming experience and counseling frequency.Key words: frontier, onion farming, technical efficiency